2015
DOI: 10.1038/icb.2015.43
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis infection of the ‘non‐classical immune cell’

Abstract: Mycobacterium tuberculosis can infect 'non-classical immune cells', which comprise a significant constituency of cells that reside outside of those defined as 'classical immune cells' from myeloid or lymphoid origin. Here we address the influence of specific 'non-classical immune cells' in host responses and their effects in controlling mycobacterial growth or enabling an environment conducive for bacilli persistence. The interaction of M. tuberculosis with epithelial cells, endothelial cells, fibroblasts, adi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 100 publications
(251 reference statements)
1
35
0
Order By: Relevance
“…Mtb interacts with multiple cell types [12,13] and triggers complex tissue changes [14]. Versatility of Mtb regarding its subcellular niches and its facultative intracellular replication correlates with an intricate pathology picture.…”
Section: Mtb and Its Subcellular And Lung Compartmentalizationmentioning
confidence: 99%
“…Mtb interacts with multiple cell types [12,13] and triggers complex tissue changes [14]. Versatility of Mtb regarding its subcellular niches and its facultative intracellular replication correlates with an intricate pathology picture.…”
Section: Mtb and Its Subcellular And Lung Compartmentalizationmentioning
confidence: 99%
“…Infection of alveolar epithelium triggers host protective responses such as secretion of chemokines and cytokines, nitric oxide production and antigen presentation to Mtb-specific non-classical CD8+ T cells [282]. With regard to HDTs, research has focused on modulating MMP activity of alveolar epithelial cells.…”
Section: Airway Epithelial Cellsmentioning
confidence: 99%
“…Examination of autopsy samples from individuals with TB has revealed that these cells can be infected with Mtb in vivo [282].…”
Section: Airway Epithelial Cellsmentioning
confidence: 99%
“…AECs also interact with other cells of the innate immune system, such as granulocytes, monocytes, macrophages, and innate lymphoid cells, to mount an effective defence against the invading pathogen as well as to activate the following specific immunity. AECs are now recognized as active participants of the immune response against Mtb [32] . In this study, we analysed mycobacteria-induced epithelial signalling pathways and the contribution of GPCRs to further elucidate these responses.…”
Section: Mycobacteria Manipulate G-proteincoupled Receptors To Increamentioning
confidence: 99%